Nanomechanics of a fibroblast suspended using point-like anchors reveal cytoskeleton formation. Issue 29 (2nd March 2016) - Fusco, Sabato; Memmolo, Pasquale; Miccio, Lisa; Merola, Francesco; Mugnano, Martina; Paciello, Antonio; Ferraro, Pietro; Netti, Paolo A.
Abstract : Cells are suspended and stretched using two microbeads. The formation of inner cytoskeleton structures is reported using displacement, QPM phase change and fluorescent micrographs. Abstract : In an attempt to better elucidate the material–cytoskeleton crosstalk during the initial stage of cell adhesion, here we report how suspended cells anchored to point-like bonds are able to assemble their cytoskeleton when subjected to mechanical stress. The combination of holographic optical tweezers and digital holography gives the cell footholds for adhesion and mechanical stimulation, and at the same time, acts as a label-free, force-revealing system over time, detecting the cell nanomechanical response in the pN range. To confirm the formation of the cytoskeleton structures after the stimulation, a fluorescence imaging system was added as a control. The strategy here proposed portends broad applicability to investigate the correlation between the forces applied to cells and their cytoskeleton assembly process in this or other complex configurations with multiple anchor points.